2012
DOI: 10.1186/1471-2458-12-1094
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary approach to management of maternal asthma (MAMMA [copyright]): the PROTOCOL for a randomized controlled trial

Abstract: BackgroundUncontrolled asthma during pregnancy is associated with the maternal hazards of disease exacerbation, and perinatal hazards including intrauterine growth restriction and preterm birth. Interventions directed at achieving better asthma control during pregnancy should be considered a high priority in order to optimise both maternal and perinatal outcomes. Poor compliance with prescribed asthma medications during pregnancy and suboptimal prescribing patterns to pregnant women have both been shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 27 publications
(30 reference statements)
1
63
0
2
Order By: Relevance
“…12,13 Studies have demonstrated several improved outcomes as a result of a Multi-D approach to complex maternal-fetal care, including changes in diagnosis, antenatal and postnatal management, timing of delivery, improvement in emotional, social and financial family well-being, and implementation of protocols that improve long-term outcomes. [12][13][14][15][16][17] In 2011, the American College of Obstetricians and Gynecologists recommended that the organization and governance of centers involved in fetal intervention should involve a Multi-D team of health care providers. 18 For several reasons, MFM specialists are well suited to coordinate Multi-D care of the complex maternal-fetal dyad: they are often the first member of the team to interact with the patient and therefore possess a unique opportunity to establish rapport and trust with the family, 8 and, by nature of their subspecialty training and knowledge of abnormal maternal and neonatal physiology may refine the fetal diagnosis, alter the antepartum management or guide the intrapartum process with the help of additional subspecialty providers.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies have demonstrated several improved outcomes as a result of a Multi-D approach to complex maternal-fetal care, including changes in diagnosis, antenatal and postnatal management, timing of delivery, improvement in emotional, social and financial family well-being, and implementation of protocols that improve long-term outcomes. [12][13][14][15][16][17] In 2011, the American College of Obstetricians and Gynecologists recommended that the organization and governance of centers involved in fetal intervention should involve a Multi-D team of health care providers. 18 For several reasons, MFM specialists are well suited to coordinate Multi-D care of the complex maternal-fetal dyad: they are often the first member of the team to interact with the patient and therefore possess a unique opportunity to establish rapport and trust with the family, 8 and, by nature of their subspecialty training and knowledge of abnormal maternal and neonatal physiology may refine the fetal diagnosis, alter the antepartum management or guide the intrapartum process with the help of additional subspecialty providers.…”
Section: Discussionmentioning
confidence: 99%
“…This restricts the generalisability of this approach given the high proportion of asthmatic women who also smoke during pregnancy (420%) [3]. In addition, it has been suggested that the applicability of F E NO to routine clinical settings may be further limited due to issues around clinical expertise, expense and accessibility [7]. Most important, use of FENO is not a stand-alone approach towards improving asthma management, and does not replace the need for appropriate asthma self-management education.…”
mentioning
confidence: 99%
“…Therefore, current asthma management appears to be focused on a reactive, not proactive, approach. This is highlighted through only 5-15% of asthmatic pregnant women involved in previous studies reporting having a current asthma action plan [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…295 It is feasible for this to be achieved by pharmacist-clinician collaboration, with monthly telephone monitoring of asthma symptom control. 296 Respiratory infections should be monitored and managed appropriately during pregnancy. 289 During acute asthma exacerbations, pregnant women may be less likely to be treated appropriately than non-pregnant patients.…”
mentioning
confidence: 99%